The abiotic stress gene (Asg) family member Asg2 as a modulator of plant responses to salt stress - Xiaona Tian; Ziru Chang; Ruigang Wang; Guojing Li; Yang Qi (Plant Stress)
The Abiotic Stress Gene (Asg) family, unique to plants, includes members with the DUF1005 domain of unknown function (DUFs). Although earlier studies have associated members of the Asg gene family and various aspects of plant growth, development, and reactions to abiotic stress, their precise biological roles and underlying mechanisms are not yet well understood. This research found that Asg2 functions not only in regulating root development but also serves as an inhibitor in how the plant responds to salt stress. Overexpression of Asg2 enhances primary root elongation, while gene-edited mutants display the opposite effect. Under salt stress conditions, Arabidopsis lines with increased Asg2 expression exhibit inhibited primary root elongation, reduced seed germination rates, and heightened sensitivity of leaves and seedlings to salt stress. These changes coincide with increased electrolyte leakage, reduced chlorophyll content, decreased antioxidant enzyme activity, and elevated levels of reactive oxygen species (ROS). Transcriptomic analysis revealed that overexpression of Asg2 under salt stress leads to the downregulation of stress resistance genes, thereby increasing sensitivity to salt stress. In conclusion, this research emphasizes the important function of the Asg gene in influencing salt tolerance, providing a foundational framework and genetic resource for comprehending how plants respond to salt stress.